Forms and Techniques of Learning Evaluation Instruments in Elementary School - Armawati Armawati; Susilasari Susilasari; Afifah Dwi Ramadhani (Lembaran Ilmu Kependidikan, 2026)
This study aims to comprehensively examine the forms of learning evaluation instruments and evaluation techniques applied in Islamic Elementary Schools (MI/SD), including the problems and trends in their implementation. The research method used is a literature review by examining relevant national scientific journal articles published between 2017 and 2025. Data were obtained through searching and selecting literature discussing learning evaluation, assessment instruments, authentic assessment, and the use of technology in learning evaluation at the elementary education level. Data analysis was conducted descriptively and qualitatively through content review and synthesis of previous research findings. The results show that the forms of learning evaluation instruments in MI/SD theoretically include test and non-test instruments that assess students' cognitive, affective, and psychomotor aspects. However, in practice, learning evaluation is still dominated by written tests oriented towards lower-level cognitive abilities. Non-test evaluation techniques, authentic assessment, and formative evaluation have not been optimally implemented due to limited teacher understanding, assessment subjectivity, administrative burden, and the lack of use of standardized rubrics. Furthermore, the use of technology in learning evaluation is growing, but it still tends to replace conventional techniques without significant innovation. This study concludes that strengthening teacher competencies and institutional support is needed to develop more varied, authentic, and appropriate forms and techniques for learning evaluation instruments tailored to the characteristics of MI/SD students to improve the quality of learning processes and outcomes.